Recent advances in marine biotechnology (Science Pub., 2000)
This volume, along with Part A "Seaweeds and Invertebrates", presents information that can be used to facilitate the aquaculture of a wide variety of food species. Possible solutions as to how to control the life cycles of important food organisms are included.